Rainfall analysis in the Central-South Region of Ceará: A study of the period (1980-2009) (Research, Society and Development, 2020)
The history of the northeastern semi-arid region is closely linked with periods of prolonged droughts and few years with heavy rains, presenting great potential to cause several negative effects to society, such as: unemployment, hunger, poverty, rural exodus, energy consumption, thermal comfort and tourism. Therefore, the rains in this region are of paramount importance for carrying out agricultural activities, environmental and urban planning, electricity generation, dimensioning of works in Sanitary and Hydraulic Engineering, management of water resources and river basin planning. Knowing the rainfall regime of a given region can corroborate the various sectors of society. This work aims to analyze the behavior of rainfall occurred in the Central-South Region of Ceará in the period from 1980 to 2009. To carry out the research, the data were made available by the Secretary of Water Resources of Ceará (SRH) from meteorological stations of the Ceará Foundation of Meteorology and Water Resources (FUNCEME) through historical series. Descriptive statistical calculations were performed using excel software, such as: mean, median, standard deviation (SD), variance, minimum value, maximum value, amplitude and coefficient of variation (CV). The results obtained show a temporal and spatial irregularity in the rainfall regime in the municipalities in question, characterized by high interannual, seasonal and intraseasonal atmospheric variability.